Enhanced Degradation of Melanoidin and Caramel in Biomethanated Distillery Spentwash by Microorganisms Isolated from Mangroves - Nagaraj Naik; K.S. Jagadeesh; M.N. Noolvi (Iranica Journal of Energy and Environment, 2010)
Four microorganisms isolated from samples of mangrove areas were found to be promising and significantly decolorized spent wash. Incidentally, they showed higher phenol degradation and COD reductionas well. The individual colorants imparting the color to spent wash were fractionated. Degradation of melanoidin and caramel was confirmed by UV and FTIR spectral analysis. Decrease in OD of melanoidin and caramel at their 8 max and appearance of new peaks and changes in functional groups of compounds in the IR spectra with respect to control suggest their degradation. K1 was the best melanoidin (77%) as well as caramel (54%) degrader followed by other three isolates (Ku3, Rtb2 and EB4).